Posttraumatic stress symptoms in nonexposed, victims, and spontaneous rescuers after an avalanche - Johnsen, Bjørn Helge; Eid, Jarle; Løstad, Terje; Michelsen, Leif Tore (Journal of traumatic stress, 1997)
A company from the Norwegian Army was investigated 2 weeks and 4 months after they were hit by an avalanche during a winter exercise. The subjects were divided into victims, spontaneous rescuers, and nonexposed subjects. The results showed that exposed subjects (victims and rescuers) reported higher levels of symptoms compared to nonexposed subjects. No differences were found among exposed subjects. The level of symptoms was also higher than comparable previous research both on victims and professional rescuers or nonprofessionals assigned a role as rescuers. All groups showed decrement in symptoms on the 4‐month follow‐up.